Հյուսիսարևելյան Հայաստանի մելիքությունները XVII դարում - Եսայան, Անդրանիկ (Մատենադարան)
The war between Ottoman Turkey and Safavid Iran, which lasted more than one and a half century, ended in 1639 with the conclusion of the Kasre-Shirin peace treaty. It was followed by a 90-years period of peace between the two countries. According to the treaty, among other Armenian territories, Northeastern Armenia again passed to Safavid Persia. Although Northeastern Armenia did not escape the disasters that plagued Armenia during the reign of Shah Abbas (reigned 1587–1629), in contrast to its other parts, deportations in Northeastern Armenia were not massive and systematic. However, the demographic picture of Northeastern Armenia significantly changed since the 16th century, when the region was settled by different nomadic tribes. The Muslim population began to grow in the region. The Armenian people continued to live in mountainous areas. Several Melikdoms aroused there, the most notable of which were the Melikdoms of Tavush, Shatakh, Miap‘or and Kunen. Война между Сефевидской Персией и Османской империей, пpoдлившаяся почти полтора века, закончилась в 1639 в г. Касре Ширинским мирным договором. Затем последовал 90-летний период мира между двумя странами. В соответствии с этим договором, вместе с другими армянскими территориями, северо-восточная Армения вновь перешла к Сефевидской Персии. Несмотря на то, что северо-восточная Армения не избежала бедствий, преследовавших Армению во время правления шаха Аббаса (1587-1629 гг.), в отличие от других ее частей, она не подвергалась массовой и систематической депортации. Однако демографическая картина в этих районах Армении стала меняться начиная с 16-го века, когда там стали селиться различные кочевые племена.Число мусульманского населения возрастало. Армянское население продолжало жить в горных районах. Там сформировались некоторые меликства, из которых наиболее заметными были меликства Тавуша, Шатаха, Миапора и Кунена.
Keywords: Պատմություն